Ho Chi Minh and Russia (On the 100th anniversary of Ho Chi Minh's first arrival to our country on June 30, 1923) - Kobelev E.V. (Восточная Азия: факты и аналитика, 2023)
The essay tells about a landmark event in Russian-Vietnamese relations – the opening of a bronze monument to the leader of the Vietnamese people Ho Chi Minh on June 30, 2023 in St. Petersburg on the occasion of the 100th anniversary of his first arrival in Russia. Thanks to Ho Chi Minh, Russian-Vietnamese relations from the very beginning acquired the character of “relationships of special solidarity”. The author reveals the personality traits of Ho Chi Minh and his ideology. First of all, it is historical optimism and absolute faith in the victory of a just cause – the freedom and independence of Vietnam, as well as humanity and rare modesty. He had truly unlimited authority among his people, but it was not a cult of personality. The author concludes that Ho Chi Minh deeply studied the practical experience of the October Revolution, which allowed him to blaze a path in leading the Vietnamese revolution that most closely corresponded to the peculiarities of the political development of Vietnam and the national mentality. Ho Chi Minh initiated the strategy of a united front of national liberation. The Viet Minh Front, created by him in May 1941, was open to all Vietnamese patriots, regardless of their class and social affiliation. It was under the flags of the Viet Minh that the August Revolution of 1945, one of the most bloodless revolutions in world history, won. The author shows the significance of Ho Chi Minh’s political activity alternately in Russia and China in 1923–1940, and then the decisive role of the two socialist powers in the victorious end of the long-term war of Resistance of the Vietnamese people against the colonialists. Therefore, Ho Chi Minh, according to the author, had a hard time with the steady deterioration of Soviet-Chinese relations in 1950–1960. This was reflected, in particular, in his Political Testament. The essay shows that in the years preceding the victory of the August Revolution in Vietnam, Ho Chi Minh spent more than six years in the USSR. After becoming the President of the DRV, he also repeatedly visited the Soviet Union. It is no coincidence that he was called both in Vietnam and in Russia a man who “laid the foundation of fraternal friendship” between the peoples of our countries and contributed in every possible way to its development and strengthening.